Physical activity and quality of life in adolescents and orphans - Lucija Maglica; Hrvoje Karninčić; Ana Penjak; Gordan Drašinac (University of Novi Sad, Faculty of Sport and Physical Education, 2020)
The aim of this study was to determine the relationship between physical activity and the quality of life in secondary school pupils and in orphans. The second aim was to determine differences in physical activity habits among groups. 91 participants (age 15.4±1.2) divided in two subsamples: secondary school pupils (n=75) and orphans from Split region (n=16). The variable sample consisted of nine variables out of which four variables that questioned the quality of life by means of the World Health Organization Quality of Life questionnaire and five of them questioned subjective assessment of weekly physical activities by means of The International Physical Activity Questionnaire. Differences between groups were tested by Mann-Whitney U test. Correlation among the quality of life self-assessment variable and weekly physical activity habits in total sample and for both groups separately, were established by Spearman coefficient rank. Differences between groups were found in the variable of light physical activity intensity level (U=376.5; Z=-2,3; p=0.02). Although housekeeping activity in orphan's institution is performed by employees, orphans participate more than peers. Intensive physical activity among orphans significantly correlates with social aspect (ρ=0.58) and surroundings aspect of the quality of life (ρ=0.62). Orphans share similar amount of physical activities with other pupils but sport has particular meaning for them. The more sports they do, the more satisfied regarding the social domain of quality of life they feel.